Potential kidney toxicity from the antiviral drug tenofovir: new indications, new formulations, and a new prodrug. Issue 2 (March 2018) - Chan, Lili; Asriel, Benjamin; Eaton, Ellen F.; Wyatt, Christina M.
Abstract : Purpose of review: The antiviral agent tenofovir is highly effective for the treatment of HIV and hepatitis B virus infections, and the older prodrug tenofovir disoproxil fumarate (TDF) is also a component of daily preexposure prophylaxis (PrEP) to reduce the risk of HIV infection in high-risk populations. Although TDF is well tolerated, the potential for kidney and bone toxicity has important implications for public health given the large number of individuals exposed to TDF worldwide. This review summarizes the recent literature on kidney and bone health in individuals treated with TDF and the newer prodrug tenofovir alafenamide (TAF). Recent findings: Risk factors for TDF toxicity appear to be similar in patients treated for HIV or hepatitis B virus and in HIV-uninfected PrEP users, although drug–drug interactions are a more important concern in HIV-positive individuals. The risk of toxicity appears to be lower with TAF, but further studies are needed to confirm the safety of long-term use and to evaluate the efficacy of TAF-based PrEP. Summary: Nephrologists should be aware of the potential kidney and bone toxicity of TDF, as well as unique situations in which the newer prodrug TAF may contribute to kidney injury.